DESIGN OF PRODUCTION PROCESS IMPROVEMENT TO DECREASE DEFECT PRODUCT FOR SANDALS AT PT X USING SIX SIGMA METHODOLOGY - Rachmawati, Hani
PT X is one of companies engaged in manufacturing with its main production is footwear products such as shoes and mountain sandals. Based on data from April to June 2019, sandals produced by PT X mostly failed (according to the AQL table) compared to other products in the Cementing Division which is 28 times. There are 1404 pairs major defect product in sandals from total of 12142 pairs. In other words, the proportion of major defect products during this period is 11.56%. Methodology used in this study is the Six Sigma methodology with DMAIC stages (Define, Measure, Analyze, Improve, and Control). Stage of Define aims to determine the object of research and focused issues to be discussed, namely efforts to decrease the number of defect products for sandals at PT X. Stage of Measure aims to measure the conditions of the current production process by measuring the stability and capability of the process. The measurement result of the process stability using control chart shows that in general, sandal production process is currently stable. The measurement result of the capability process by measuring sigma level showing value of 2,27 sigma. That value has not met yet the company value target (3 sigma) and value 6 sigma. Stage of Analyze aims to determine the root cause of the defect problem and determine the priority of problem to be solved. In this stage pareto chart are being used to choose defect type that will be further researched, namely Rocking and Toespring Difference. Identification root cause of the defect are being done using delphi method, then determining problem priority using Failure Mode and Effect Analysis (FMEA). The results of the Define, Measure, and Analyze stages are further researched at Improve and Control stages. Stage of Improve aims to arrange, choose, and design alternative solutions for prioritized problems. Eight out of ten alternative solutions proposed were accepted by the company. Stage of Control aims to monitor the implementation of the solution which has been designed in the Improve stage. Supervision is carried out by preparing timeline to implement the solution and improving the Work Instruction document.